Analytical derivation and numerical test of novel scaling laws for air-water flows - Catucci, Daniele (2023)
Physical modelling at reduced size is one of the oldest and most important design tools in hydraulic engineering. To predict the behaviour of the prototype, a physical model needs to incorporate all involved forces. The Froude scaling laws are being used to model a wide range of water flows at reduced size for almost a century. They are based on the invariance of the Froude number, i.e. the square root of the ratio between the inertial and gravity force between the model and its prototype. However, scale effects are observed due to forces excluded from the Froude number, for example in air-water flows, such as hydraulic jumps or wave breaking, the viscous, surface tension and air compressibility forces are scaled incorrectly at reduced size.